Perspectives on Endosymbiosis in Coralloid Roots: Association of Cycads and Cyanobacteria - Chang, Aimee Caye G.; Chen, Tao; Li, Nan; Duan, Jun (Frontiers in Microbiology, 2019)
Past endosymbiotic events allowed photosynthetic organisms to flourish and evolve in terrestrial areas. The precursor of chloroplasts was an ancient photosynthetic cyanobacterium. Presently, cyanobacteria are still capable of establishing successful symbioses in a wide range of hosts. One particular host plant among the gymnosperms is cycads (Order Cycadales) in which a special type of root system, referred to as coralloid roots, develops to house symbiotic cyanobacteria. A number of studies have explained coralloid root formation and cyanobiont invasion but the questions on mechanisms of this host-microbe association remains vague. Most researches focus on diversity of symbionts in coralloid roots but equally important is to explore the underlying mechanisms of cycads-Nostoc symbiosis as well. Besides providing an overview of relevant areas presently known about this association and citing putative genes involved in cycad-cyanobacteria symbioses, this paper aims to identify the limitations that hamper attempts to get to the root of the matter and suggests future research directions that may prove useful.